Supporting Strategic Intuition for Product Feature Innovation in Early-Stage Fintech Payments Start-ups - Sri Handoko; Nanik Qosidah (University of Science and Computer Technology, 2025)
Early-stage fintech payments start-ups face high uncertainty, limited historical data, and compressed decision cycles, making product feature innovation both critical and fragile. Despite growing attention to AI-supported tools and data-driven strategies, little is known about how strategic intuition guides product decisions in these contexts. This study develops a conceptual and practice-based framework to explore how strategic intuition, supported by digital leadership and human–AI collaboration, shapes feature ideation, prototyping, and prioritization processes. Using simulated product decision scenarios and data dummy analysis, the research maps decision points across development stages and examines how teams integrate intuitive judgment with analytical cues. Findings reveal that strategic intuition functions as a central mechanism for aligning feature choices with strategic goals, enhancing coherence and adaptability under uncertainty. Digital leadership legitimizes intuitive decisions, fosters cross-functional collaboration, and creates a psychologically safe environment, while AI tools complement rather than replace human judgment. The study contributes theoretically by positioning strategic intuition as a core element of product feature innovation in early-stage ventures and by integrating cognitive, social, and technological mechanisms into a unified framework. In practice, the framework provides actionable guidance for start-up teams to improve decision quality and speed without relying on costly field experiments, offering insights for managers, incubators, and policymakers seeking to support innovation under constraints. Overall, the research underscores the value of structured intuition as a deliberate, analytically informed process that advances understanding of cognition-supported innovation in nascent digital ventures.